A cross-sectional study on nutrient intake and -status in inflammatory bowel disease patients. Issue 1 (December 2015) - Vidarsdottir, Jona; Johannsdottir, Sigridur; Thorsdottir, Inga; Bjornsson, Einar; Ramel, Alfons
Abstract Background and aims Inflammatory bowel disease (IBD) can be associated with nutritional problems. The aim of this study was to investigate diet and nutritional status of IBD patients. Methods A total of 78 participants (35 men and 43 women aged 18–74 years) were included in this cross-sectional study. The majority (80 %) of the participant received infliximab treatment. Participants filled out disease related questionnaires and 31 participants also a 3-day food record. Body composition was measured and blood samples analysed in order to estimate nutritional status. Results The majority (87 %) claimed that diet affects digestive tract symptoms and 72 % had changed diet accordingly. The most common foods restricted were dairy products (60 %), processed meat (55 %), soft drinks (46 %), alcohol (45 %) and fast food (44 %). Body mass index was mostly in the overweight range but 46 % of the participants had been diagnosed with some nutritional deficiency since IBD diagnosis (most common was iron deficiency: 39 %). Patients who restricted meat products had lower ferritin values (48 ± 39 vs. 95 ± 74 μg/L, P  = 0.011). Intake of vitamin D and calcium were not adequate (65 % below recommeded intake for both) and 60 % had poor vitamin D status. Conclusion IBD patients often change their dietary intake in order to affect digestive tract symptoms. Many patients have a history of nutrient deficiency. Restriction of dairy and meat consumption is common and is negatively associated with intake or status of micronutrients like calcium and iron. Dietary advice by a dietitian and use of potentially helpful dietary supplements is indicated.